Impact of Profitability, Capital Structure, and Firm Size on Pharmaceutical Company Valuation: Evidence from Indonesia: Dampak Profitabilitas, Struktur Modal, dan Ukuran Perusahaan pada Penilaian Perusahaan Farmasi: Bukti dari Indonesia - Riza Yuana; Heri Widodo (Academia Open, 2024)
This study aims to examine the influence of profitability, capital structure, and firm size on the valuation of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the period 2015-2020. The research population comprises all pharmaceutical firms listed during this period, totaling eight companies. Employing a saturated sampling technique, the study utilizes all eight companies as its sample. Data analysis involves multiple linear regression using SPSS version 26. The results reveal that profitability, proxied by Return On Asset (ROA), capital structure, proxied by Debt to Equity Ratio (DER), and firm size, proxied by Total Assets, exert a positive and significant impact on company valuation, measured by Price to Book Value (PBV), with a substantial explanatory power of 73%, leaving 27% of the variation unaccounted for by the variables examined in this study. These findings contribute to a better understanding of the determinants of pharmaceutical company valuation and have implications for investors, policymakers, and researchers in the global pharmaceutical industry.Highlights : This study investigates the impact of profitability, capital structure, and firm size on the valuation of pharmaceutical firms in the Indonesian stock market from 2015 to 2020. The research utilizes a saturated sampling technique, including all eight pharmaceutical companies listed during the study period. Findings reveal a significant positive relationship between profitability, capital structure, firm size, and company valuation, shedding light on critical factors influencing pharmaceutical company performance in the global market. Keywords: Pharmaceutical companies, Valuation, Profitability, Capital Structure, Firm Size